2006
DOI: 10.2169/internalmedicine.45.6005
|View full text |Cite
|
Sign up to set email alerts
|

An Adult Case with Hunters Syndrome Presenting Prominent Hepatic Failure: Light and Electron Microscopic Features of the Liver

Abstract: We describe a 40-year-old

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 8 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…This finding is consistent with the results of Resnick, et al,8 who reported fibrotic changes in liver biopsy samples from 27 infant MPS cases. Hepatic fibrosis in patients with MPS has been reported in the literature, mainly in adult cases 9,10. Parfrey and Hutchins suggested that hepatic fibrosis is due to abnormal accumulation of hepatotoxic metabolites 9.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with the results of Resnick, et al,8 who reported fibrotic changes in liver biopsy samples from 27 infant MPS cases. Hepatic fibrosis in patients with MPS has been reported in the literature, mainly in adult cases 9,10. Parfrey and Hutchins suggested that hepatic fibrosis is due to abnormal accumulation of hepatotoxic metabolites 9.…”
Section: Discussionmentioning
confidence: 99%